Calceolariaceae endémicas del Perú - Salinas, Irayda (2006)
The Calceolariaceae are represented in Peru by two genera and 121 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly shrubs and herbs. Here we recognize 101 endemic taxa, most of them in the genus Calceolaria. Endemic taxa are found mostly in the Mesoandean, Humid and Dry Puna, and Paramo regions, between 300 and 4500 m elevation. Twenty seven endemic taxa have been recorded within the Peruvian parks system.